2015
DOI: 10.4103/1319-2442.148741
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the opinion of hemodialysis patients about their dialysis unit

Abstract: Hemodialysis (HD) patients are subjected to a number of physical and mental stresses. Physicians might be unaware of some of these problems. We assessed our patients' opinion about the service provided at the dialysis unit. Our unit has 89 patients on HD. A questionnaire exploring our patients' opinion relative to the service provided was prepared. The patients were asked to fill-in the questionnaire in a confidential manner. Questionnaires were then collected and examined while unaware of patient identities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
4
6
0
Order By: Relevance
“…In addition, 34.3% of our patients wished that the medical staff of the Haemodialysis Unit was more approachable, whereas 97.1% stated that the nursing staff was caring and easy to communicate with. This result is also in accordance to other studies that found patients to be in closer contact with the nursing staff than with physicians in general and during the greater part of the haemodialysis session [16,[20][21][22]. Furthermore, in a recent study, the majority of the patients observed, that even though they were satisfied with the care they received in general, they weren't satisfied with the amount of time they spent with the doctors of the Haemodialysis Unit [19].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, 34.3% of our patients wished that the medical staff of the Haemodialysis Unit was more approachable, whereas 97.1% stated that the nursing staff was caring and easy to communicate with. This result is also in accordance to other studies that found patients to be in closer contact with the nursing staff than with physicians in general and during the greater part of the haemodialysis session [16,[20][21][22]. Furthermore, in a recent study, the majority of the patients observed, that even though they were satisfied with the care they received in general, they weren't satisfied with the amount of time they spent with the doctors of the Haemodialysis Unit [19].…”
Section: Discussionsupporting
confidence: 93%
“…According to our study results, 77.1% of the patients were satisfied in general by the healthcare provided at the Haemodialysis Unit and 88.6% were satisfied by the interest shown for their individual needs. This is similar to other studies, where patients very rarely evaluated the services provided as "bad" and the level of satisfaction with interpersonal care was high [16,18]. In a more recent study, as well, the percentage of the patients satisfied with the care provided at the Haemodialysis Unit was 82.56%, similar to the one found by our research [19].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings add to the current literature on patient perspectives of care in dialysis units and are consistent with research that indicates there may be differences in the priorities and preferences of patients compared to those of health professionals . In line with our findings, many of these studies indicate that procedural elements of care may have more salience over health outcomes to dialysis patients.…”
Section: Discussionsupporting
confidence: 90%
“…The findings add to the current literature on patient perspectives of care in dialysis units and are consistent with research that indicates there may be differences in the priorities and preferences of patients compared to those of health professionals. 4,6,[12][13][14] In line with our findings, many of these studies indicate that procedural elements of care may have more salience over health outcomes to dialysis patients. Studies suggest patients particularly value interaction with health care professionals, the physical environment and atmosphere of the dialysis unit, the quantity and quality of information provided by staff to patients about their condition, respect for confidentiality and appropriate management of patient data, and the quality of patient transportation.…”
Section: Discussionsupporting
confidence: 87%